Young peoples' perspective on the portrayal of alcohol and drinking on television: Findings of a focus group study. (April 2013) - Atkinson, Amanda Marie; Bellis, Mark; Sumnall, Harry
<x xml:space="preserve">Abstract</x> This article presents findings of focus groups (n = 15) with young people (n = 114) which aimed to explore their views, experiences and interpretations of the ways in which alcohol and drinking are portrayed on television. Young people showed a sophisticated level of awareness of alcohol and its use on television and were adept at deconstructing the alcohol-related messages presented. Participants were undecided as to whether they believed television represented alcohol use in a realistic manner and acknowledged a contradiction between realistic accounts and exaggeration for the creation of 'entertaining' content. Overall, participants felt that television should provide a balanced view of alcohol use, showing both the positive side of drinking and the possible negative effects without an overemphasis on the latter. Young people did perceive television to exert an influence upon audiences. However, a 'third person effect' was found, with participants speaking in the third person and suggesting that television may influence others, but not themselves. The implications of the findings are discussed in relation to the potential influence of these representations on the development of alcohol-related beliefs and behaviour and the use of television in alcohol-related health promotion.